PENERAPAN FUNGSI MANAJERIAL DALAM PENINGKATAN EFISIENSI PENDIDIKAN DI SD NEGERI CANDIREJO 02 - Ardhani, Rina; Muji, Sri; Praseptiana, Chory; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research aims to analyze the application of managerial functions in improving educational efficiency at SD Negeri Candirejo 02. The focus of the research includes planning, organizing, directing and controlling implemented by headmaster, as well as their impact on educational efficiency. The method used in this research is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that the implementation of managerial functions in this school has a positive impact on educational efficiency, although there are still several obstacles that need to be overcome. Planning and organizing is going well, but aspects of direction and control require improvement, especially in terms of routine monitoring and evaluation. Educational efficiency is quite optimal, although limited facilities and infrastructure and a lack of technology training for teachers. Collaboration between school principals, teachers and parents also contributes positively, but communication and resource management still need to be improved. In conclusion, improvements in several managerial aspects can further increase learning efficiency at SD Negeri Candirejo 02.